Pacific Asia in the global system : - Preston, P. W. (Blackwell, 1998)
Introduction will serve as a 'first stop' for those interested in Japan, its role in the Pacific Asian region and, in turn, that region's role in the evolving global system. In this volume, P. W. Preston critically analyses the political economy, social institutions and culture of Pacific Asia. The analysis focuses on Japan , it's relations with the inner periphery of Southeast Asia, and its developing linkages with the reforming socialist countries of China and Indo-China